Narratives of most significant change to explore experiences of caregivers in a caregiver-young adolescent sexual and reproductive health communication intervention in rural south-western Uganda - Akatukwasa, Cecilia; Kemigisha, Elizabeth; Namatovu, Shakira; Fernandes, Danielle; Achen, Dorcus; Mlahagwa, Wendo; Ruzaaza, Ndaruhutse; Coene, Gily; Rukundo, Godfrey Zari; Michielsen, Kristien; Nyakato, Viola N. (Plos one, 2023)
Background: This paper presents findings from a qualitative effectiveness evaluation of an intervention aimed at improving caregiver-young adolescent sexual and reproductive health (SRH) communication including training modules for caregivers on parent-child SRH communication. Methods: Data was collected (October 2021-November 2021) using a narrative interviewing technique with thirty caregivers (8 males and 22 females), who received the parent-child communication intervention in Mbarara district, south-western Uganda. We explored caregivers’ experiences with the intervention based on four domains of change: caregiver-young adolescent Communication on SRH issues, knowledge and attitudes towards adolescent SRH, parenting skills, and personal life and family. Thematic analysis was used to code and analyse the data, with attention to gender differences. Results Findings highlight positive parenting as a key attribute of SRH communication, along with a transformation of knowledge and attitudes towards the SRH of young adolescents leading to an overall improvement in SRH communication. However, communication is still limited to comfortable topics. Conclusion: Our findings indicate improved caregiver–adolescent SRH communication practices following a community intervention. Programming for adolescent health on broader sexuality topics, comfortability and attitude change among caregivers could promote behaviour change on a long term. Future studies may focus on the long term impacts of interventions of this nature and test interventions aimed at addressing comfortability with discussing SRH issues.